2013
DOI: 10.3346/jkms.2013.28.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics and Risk Factors of Retinal Vein Occlusion: A Study by the Korean RVO Study Group

Abstract: We investigated the demographic characteristics and risk factors of Korean patients with naÏve central or branch retinal vein occlusion (CRVO or BRVO). This study enrolled 41 clinical sites throughout Korea and included 557 consecutive patients with retinal vein occlusion (RVO) from May through November 2010. A total of 557 patients with new-onset RVO participated in this study. Two hundred and three (36.4%) patients were diagnosed with CRVO and 354 (63.6%) patients were diagnosed with BRVO. Comparisons betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 24 publications
2
42
2
1
Order By: Relevance
“…BRVO was highly associated with arterial hypertension and atrial fibrillation. The associations of BRVO with arterial hypertension were in line with those found in other studies . The role of diabetes mellitus remains controversial in the literature .…”
Section: Discussionsupporting
confidence: 89%
“…BRVO was highly associated with arterial hypertension and atrial fibrillation. The associations of BRVO with arterial hypertension were in line with those found in other studies . The role of diabetes mellitus remains controversial in the literature .…”
Section: Discussionsupporting
confidence: 89%
“…24 A similar result was found in a Korean study that included data on 203 patients with CRVO (36.4%) and 354 patients with BRVO (63.6%). 25 The age for presentation in this study ranged from 11 years to 82 years. In the Ocular Vascular Unit at the University of Iowa, the age range of patients was between 14 and 92 years in a series of 1108 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, age (per 10 years; odds ratio [OR], 1.47; 95% confidence interval [CI], 1.04-2.08), hypertension (OR, 4.25; 95% CI, 1.82-9.94), and hematocrit (per 10%; OR, 3.09; 95% CI, 1.10-1.22) remained independently significant risk factors for RVO. A hospital-based case-control study conducted in Nepal also confirmed a hypertension as a risk factor for RVO [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%